The role of hormonal thyroid gland pathology in hair disorders - Skrok, Anna; Kozłowska, Anna (Dermatology Review/Przegląd Dermatologiczny, 2013)
Pathology of the hypothalamus-pituitary-thyroid (HPT) axis that can lead to hypothyroidism or thyrotoxicosis is strongly connected with hair growth abnormalities. The most important for dermatologists are autoimmune thyroid diseases – Hashimoto’s thyroiditis and Graves’ disease related to various hair disorders. The most frequently observed is telogen effluvium, but there is also a connection between hormonal pathology of the thyroid gland and alopecia areata or madarosis. Hair growth abnormalities in children with congenital hypothyroidism or with atrichia with papular lesions syndrome are related to the “hairless” gene. Treatment of the thyroid gland diseases with synthetic thyroid hormones or antithyroid drugs as well as numerous other medications which can modify a hormonal balance of the thyroid gland (for example amiodarone, lithium, bexarotene, propranolol, prednisone) have a strong impact on hair growth cycle. Recently, it has been discovered that thyroid hormones, as well as TSH (thyroid-stimulating hormone) or TRH (thyrotropin releasing hormone) have receptors in the skin or in the human hair follicle, so hormones of the HPT axis can directly alter hair growth cycle. Thyroid hormones, together with estradiol so testosterone, play a role in regulation of the hair follicle metabolism so topical triiodothyronine/levothyroxine can stimulate hair follicle proliferation and anagen prolongation. Stimulation of located in the skin and in the hair follicle TSH receptors causes thyroid-specific gene expression in human skin/hair follicle, similary to that in the thyroid gland tissues. Thyrotropin releasing hormone is a new player in human hair growth control. The expression of this hormonal receptor directly in human hair follicles completes hair follicles’ hormonal axis which is totally similar to the HPT axis